2001
DOI: 10.1177/0022002701045001006
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of Politically Relevant Dyads

Abstract: Relevant dyads are pairs of contiguous states or pairs of states including at least one major power. They are argued to be the population of dyads at risk of international conflict and are increasingly commonly used as the cases analyzed by conflict researchers. Does reliance on relevant dyads (a nonrandom sample of all dyads) introduce threats to valid inference? The authors argue that relevant dyad usage might introduce related problems of measurement error and selection bias and investigate whether there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
105
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(110 citation statements)
references
References 36 publications
2
105
0
1
Order By: Relevance
“…Our results do not contradict these findings, but they do suggest the need to think further about sample selection and control variables. Lemke and Reed (2001) recently showed that although the focus on politically rele vant dyads may introduce some selection bias, it does not substantively affect the sta tistical estimates. Nonetheless, enlarging the sample to include all dyads with avail able data, thus including more distended state pairs, does weaken the estimated inverse relationship between trade and war as Oneal and Russett (1999, 431) show.…”
Section: Resultsmentioning
confidence: 99%
“…Our results do not contradict these findings, but they do suggest the need to think further about sample selection and control variables. Lemke and Reed (2001) recently showed that although the focus on politically rele vant dyads may introduce some selection bias, it does not substantively affect the sta tistical estimates. Nonetheless, enlarging the sample to include all dyads with avail able data, thus including more distended state pairs, does weaken the estimated inverse relationship between trade and war as Oneal and Russett (1999, 431) show.…”
Section: Resultsmentioning
confidence: 99%
“…Directed dyads are ordered pairs of states in which state A is the potential initiator and state B is the potential target. To eliminate dyads that have no opportunity for conflict, I restrict my analysis to "politically relevant" dyads (Lemke and Reed 2001), defined as pairs of states that are contiguous and/or include at least one major power. Out of over one million total directed dyad-years between 1945 and 2001, this restriction leaves 116,174 observations.…”
Section: Data and Measurementmentioning
confidence: 99%
“…In our first specification, following prior research designs, we restrict the study to politically relevant dyads (Lemke and Reed, 2001).…”
Section: Empirical Analysismentioning
confidence: 99%